1986
DOI: 10.1042/bj2380475
|View full text |Cite
|
Sign up to set email alerts
|

The overexpression and complete amino acid sequence of Escherichia coli 3-dehydroquinase

Abstract: The enzyme 3-dehydroquinase was purified in milligram quantities from an overproducing strain of Escherichia coli. The amino acid sequence was deduced from the nucleotide sequence of the aroD gene and confirmed by determining the amino acid composition of the overproduced enzyme and its N-terminal amino acid sequence. The complete polypeptide chain consists of 240 amino acid residues and has a calculated subunit Mr of 26,377. Transcript mapping revealed that aroD is a typical monocistronic gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…Only CNBr digestion of this enzyme was performed. As the complete amino acid sequence of E. coli 3-dehydroquinase is available from the DNA sequence of the aroD gene, which encodes this enzyme (Duncan et al, 1986; also the present paper), we were not only able to predict the exact number of CNBr-cleavage fragments that would be produced, but also their precise size and composition. We expected to find 11 peptides, ranging in size from two to 47 amino acid residues.…”
Section: Isolation Of Active-site Peptidesmentioning
confidence: 86%
See 4 more Smart Citations
“…Only CNBr digestion of this enzyme was performed. As the complete amino acid sequence of E. coli 3-dehydroquinase is available from the DNA sequence of the aroD gene, which encodes this enzyme (Duncan et al, 1986; also the present paper), we were not only able to predict the exact number of CNBr-cleavage fragments that would be produced, but also their precise size and composition. We expected to find 11 peptides, ranging in size from two to 47 amino acid residues.…”
Section: Isolation Of Active-site Peptidesmentioning
confidence: 86%
“…Subsequent digestion of the labelled protein and isolation and characterization of labelled peptides has allowed us to determine the sequence around the active-site lysine residue in 3-dehydroquinase from two species, N. crassa and E. coli. A complete nucleotide sequence for the E. coli aroD gene has been published (Duncan et al, 1986). Subsequent DNAsequencing work in our laboratory has revealed that this sequence contained errors at four locations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations